Dihydrocodeine in renal failure: further evidence for an important role of the kidney in the handling of opioid drugs. Issue 6470 (9th March 1985) - Barnes, J N; Williams, A J; Tomson, M J; Toseland, P A; Goodwin, F J
Abstract : The pharmacokinetics of a single oral dose of dihydrocodeine were studied in nine patients with chronic renal failure treated by haemodialysis and nine subjects with normal renal function. In the patients the mean peak plasma dihydrocodeine concentration occurred later and the area under the curve was greater than in the normal subjects. Furthermore, the drug was still detectable after 24 hours in all the patients but only three of the normal subjects. These data, together with those obtained from previously published clinical case reports, contradict the traditional view that the body's ability to cope with opioid drugs is not altered in renal failure.